The origins of theosophy : Annie Besant--the atheist years - Besant, Annie, 1847-1933 (Routledge revivals., 2015)
Annie Besant is primarily remembered as the international president of the Theosophical Society. One of the most important aspects of her career were the years that she was a professional atheist, which has given her a place in history as a pioneer feminist. The Origins of Theosophy contains thirteen of Besant's pamphlets, originally published from 1883-1890. This book is ideal for students of theology.